My brilliant friend - Lagani, Chiara, 1974-; Ferrante, Elena (Europa Editions, 2023)
"HBO's four-season TV adaptation of My Brilliant Friend has enjoyed success with critics and viewers in the U.S.; the novel has been adapted for the stage and radio plays. Here, for the first time, it is brought to vivid life as a graphic novel by one of Italy's most beloved illustrators. For Ferrante fans, for those new to Ferrante, for readers of graphic novels, Chiara Lagani's and Elena Ferrante's My Brilliant Friend: the graphic novel is a thrilling new adaptation of one of the best loved novels of recent decades. Translated by Ferrante's long-time translator, Ann Goldstein, the graphic novel tells the enduring story of the complex friendship between Lila and Lenù in post-war Naples"--